ZAPŁATA PODATKU A PRZEDAWNIENIE ZOBOWIĄZANIA PODATKOWEGO - Gomułowicz, Andrzej (Wydział Prawa i Administracji UAM, 2008)
Payment of tax by a tax payer is more complex that one might expect. To assume that payment of the tax results from a proper construction o f the idea of a tax obligation would be an undue simplification. A reasonable tax payer who needs to assume a certain conduct must take into account the existence o f legal regulations that will force him to fulfil his tax obligation. Those legal solutions, due to the nature of tax obligations, have a feature o f a sanction, since it is possible to effect the tax due before it falls due and before a decision imposing it has been issued, (article 33 o f the tax law.). Tax not paid on time becomes overdue tax (art. 51 ) which means that penalty interest may be calculated as provided for in the rates arising from art. 56. Having regard to the entire binding legislation, the tax payer makes a conscientious decision. It is a choice of a particular behaviour, which at the same time governs that behaviour. In other words, a tax payer makes a decision on the basis o f the causal links (understood properly or wrongly) between a certain behaviour and its legal consequences. Although the contents of art. 59 § 1 p. 1 is properly formulated from the linguistic and logical point o f view, the issue of a tax obligation becoming extinct upon its payment must be seen in a wider context. And so, the expiry o f tax obligations in the form provided for in art. 59 § 1 p .l o.p., cannot be treated separately, but the causal relationship, together with those provisions of the tax law which, taking the contents of art. 59 § 1 p. 1 as a starting point, constitute a solution which is defined as a tax institution. Therefore, the principle o f clara non sunt interpretanda may not be a premise for believing that construction and performance o f the process of interpretation is unnecessary since it does not suffice to understand the fragment o f the legal text referred to in art. 59 § 1 p . l , but it must be understood in conjunction with art. 70 § 1. Payment of a tax obligation may be an effective form o f releasing oneself from a tax obligation. It leads to the extinction of the tax obligation. In such a case, a tax obligation cannot become extinct for the second time on grounds o f having become a time-barred claim. However, a direct copy of the content of the norm contained in art. 59 § 1 p. 1 and in art. 70 § 1 of tax law does not offer an unambiguous answer when such solutions are being analysed, and in particular, when relationships between the norms within the tax law are taken into consideration. In fact, in some specific cases it is justified to construe the text of art. 59 § 1 p .l differently. The payment of a tax must be in respect of ,,a concrete amount of a tax obligation resulting from a final tax decision”. And so, the payment provided for in art. 59 § 1 p. 1 of tax law is a payment of the tax due. It will become extinct on the premise of its effective assessment. While tax extinction applies only to properly assessed tax amount, the tax obligation will not become extinct merely because it has not been assessed. Consequently, payment of tax following a tax decision that has not been final and that has been appealed against by the tax payer does not render the tax obligation extinct.
TAX OBLIGATION" VS LIMITATION OF TAX LIABILITY